2016
DOI: 10.4328/jcam.3332
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Chorionic Gonadotropin Treatment Before Testicular Sperm Extraction in Non-Obstructive Azoospermia

Abstract: ÖzetAmaç: İdiyopatik non-obstrüktif azospermili (NOA) hastalarda, ampirik hCG tedavisi ile ilgili sonuçları araştırmak. Gereç ve Yöntem: hCG grubunu normal testis hacimlerine ve normal serum FSH ve LH düzeylerine sahip olan ve ampirik hCG ile tedavi edilen 34 hasta oluşturdu. hCG, testiküler sperm ekstraksiyonundan (TESE) 10-14 hafta önce 2500 IU olarak haftada iki kere deri altına enjeksiyon şeklinde uygulandı. Kontrol grubunu yaş ve eş yaşları hCG grubu ile denk olup aynı dönemde TESE uygulanan 49 hasta oluş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In this study, fertilization rates, D3 and D5 embryo quality was found to be much better in Intracytoplasmic morphologically selected sperm injection (IMSI) than Intracytoplasmic sperm injection (ICSI). In this study, it is also said that good results were achieved when oocyte morphology was also included in evaluation [17,18]. There are similar studies as our's and also at the present time sperm DNA fragmentation is performed in many centers but still the choice for treatment is determined by a simple sperm parameters analysis in many technologically insufficient centers.…”
Section: Discussionsupporting
confidence: 56%
“…In this study, fertilization rates, D3 and D5 embryo quality was found to be much better in Intracytoplasmic morphologically selected sperm injection (IMSI) than Intracytoplasmic sperm injection (ICSI). In this study, it is also said that good results were achieved when oocyte morphology was also included in evaluation [17,18]. There are similar studies as our's and also at the present time sperm DNA fragmentation is performed in many centers but still the choice for treatment is determined by a simple sperm parameters analysis in many technologically insufficient centers.…”
Section: Discussionsupporting
confidence: 56%
“…Selective oestrogen receptor modulators [175,176], gonadotropins [177][178][179], and aromatase inhibitors [180] are commonly used to optimise sperm parameters in infertile men and as an adjunct to improve surgical sperm retrieval rates in men with NOA. However, there are no RCTs specifically analysing the benefits of hormone stimulation therapy in men with NOA and primary hypogonadism, and the literature consists of case-control studies with conflicting results [181][182][183][184][185][186]. Moreover, there is no consensus in the literature with regard to the most suitable hormone stimulation agent or regimen, and it should also be recognised that there are potential side effects associated with hormone stimulation therapy, including a paradoxical decline in serum testosterone and venous thromboembolism [174,185,187].…”
Section: Noninvasive Treatmentsmentioning
confidence: 99%
“…Non-obstructive azoospermia (NOA) refers to the detection of no sperm in semen analysis due to minimal or no production of fully developed sperms in the testicles [2]. Today, the most important advancement in the treatment of infertile male cases is detection of small foci with ongoing spermatogenesis in the testicles of NOA cases and retrieving mature sperm cells from these foci (testicular sperm extraction: TESE).…”
Section: Introductionmentioning
confidence: 99%